Antimicrobials in food - Davidson, P. Michael, 1950-; Taylor, T. M. (T. Matthew); David, Jairus R. D. (Boca Raton : CRC Press, 2021)
"Fifteen years have passed since the 3rd Edition of Antimicrobials in Foods was published. It was arguably considered the "must-have" reference for those needing information on chemical antimicrobials used in foods. In the years since the last edition, the food industry has undergone radical transformations because of changes on several fronts. Reported consumer demands for the use of "natural" and "clean-label" antimicrobials has increased significantly. The discovery of new foodborne pathogen niches and potentially hazardous foods, along with a critical need to reduce food spoilage waste, has increased the need for suitable antimicrobial compounds or systems. Novel natural antimicrobials continue to be discovered and new research has been carried out on traditional compounds. These and other related issues led the editors to develop the 4th Edition of Antimicrobials in Foods. In the 4th Edition, the editors have compiled contemporary topics with information synthesized from internationally recognized authorities in their fields. In addition to updated information, new chapters have been added in this latest release with content on the use of bacteriophages, lauric arginate ester, and various systems for antimicrobial encapsulation and delivery. Comprehensive revisions of landmark chapters in previous editions including naturally occurring antimicrobials from both animal and plant sources, methods for determining antimicrobial activity, new approaches to multifactorial food preservation or "hurdle technology," and mechanisms of action, resistance, and stress adaptation are included. Complementing these topics is new information on quantifying the capability of "clean" antimicrobials for food preservation when compared to traditional food preservatives and industry considerations when antimicrobials are evaluated for use in food manufacture"--
Food Antimicrobials -- An Introduction. Methods for Activity Assay and Evaluation of Results. Sodium Benzoate and Benzoic Acid. Sorbic Acid and Sorbates. Organic Acids. Sulfur Dioxide and Sulfites. Nitrite. Nisin. Natamycin. Lauric Arginate. Medium-Chain Fatty Acids and Esters. Parabens. Dimethyl Dicarbonate and Diethyl Dicarbonate. Lysozyme. Bacteriocins with Potential for Use in Foods. Bacteriophages. Naturally Occurring Compounds -- Plant Sources. Naturally Occurring Compounds -- Animal Sources. Sanitizers. Processing Aids as Antimicrobials. Delivery Systems. Update on Hurdle Technology Approaches to Food Preservation. Practical Application of Food Antimicrobials. Mechanisms of Action, Resistance, and Stress Adaptation.
OCLC-licensed vendor bibliographic record.
Keywords: Food additives; Anti-infective agents; TECHNOLOGY / Food Science